2007
DOI: 10.1172/jci31986
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin mediates obesity-induced adipose tissue macrophage infiltration and insulin resistance in mice

Abstract: Obesity is associated with a state of chronic, low-grade inflammation characterized by abnormal cytokine production and macrophage infiltration into adipose tissue, which may contribute to the development of insulin resistance. During immune responses, tissue infiltration by macrophages is dependent on the expression of osteopontin, an extracellular matrix protein and proinflammatory cytokine that promotes monocyte chemotaxis and cell motility. In the present study, we used a murine model of diet-induced obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
324
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(371 citation statements)
references
References 60 publications
34
324
2
1
Order By: Relevance
“…Previous studies have shown that expression of OPN is increased in diabetes, where it plays a key role in high-fat diet-induced macrophage recruitment to adipose tissue and the induction of insulin resistance (18). Moreover, OPN is upregulated in many forms of heart failure in which both gain-and loss-of-function experiments have shown that it plays a pathologic role in cardiac dysfunction (22,27,31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that expression of OPN is increased in diabetes, where it plays a key role in high-fat diet-induced macrophage recruitment to adipose tissue and the induction of insulin resistance (18). Moreover, OPN is upregulated in many forms of heart failure in which both gain-and loss-of-function experiments have shown that it plays a pathologic role in cardiac dysfunction (22,27,31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that obese adipose tissue is hallmarked with chronic, lowgrade inflammation, and that inflammation plays a central role in the development of insulin resistance (1,2). Although the contributions of the CD44 encoded protein to the molecular pathogenesis of T2D have not yet been reported, SPP1 was reported as a link between adipose tissue inflammation (stromal infiltration by inflammatory cells) and the development of insulin resistance in a murine model of diet-induced obesity (25). Furthermore, the expression profile of CD44 and SPP1 are coordinately dysregulated, especially in adipose tissue ( Fig.…”
mentioning
confidence: 99%
“…6 Beside tubular cell EMT induction, MMP-9 is known to be capable of cleaving osteopontin (OPN), 22 a macrophage chemoattractant and macrophages are well known to have a role in renal fibrosis. [23][24][25] However, whether a protection in renal fibrosis was due to a reduction of macrophage infiltration in MMP-9 KO model is unclear. Furthermore, MMPs including MMP-9 has been shown to exhibit an opposing role at different stages of disease progression including renal disease.…”
mentioning
confidence: 99%